Diagnostic Challenge of Localized Tenosynovial Giant Cell Tumor in Children - Jiro Ichikawa; Satoshi Ochiai; Tomonori Kawasaki; Kojiro Onohara; Masanori Wako; Hirotaka Haro; Tetsuo Hagino (Diagnostics)
This report describes a rare case of a pediatric tenosynovial giant cell tumor (TSGCT) with a delayed diagnosis. A 9-year-old boy presented with a 3-month history of knee pain and swelling, initially attributed to a femoral non-ossifying fibroma and arthritis based on computed tomography findings and slightly elevated C-reactive protein levels. The symptoms persisted despite medical treatment. Magnetic resonance imaging (MRI) revealed a tumor in the posterior compartment. He underwent surgery, and the pathology confirmed the diagnosis of localized TSGCT. Six months postoperatively, the patient remained asymptomatic. Pediatric knee pain is a complex symptom associated with inflammatory conditions and benign and malignant tumors. Benign tumors, as in this case, can be misdiagnosed as arthritis, delaying diagnosis and treatment. MRI is recommended in cases involving symptom persistence. However, histopathological, immunohistochemical, and morphological examinations are crucial for definitive diagnosis, particularly when the imaging findings are inconclusive.